Clinical experience and workflow challenges with magnetic resonance-only radiation therapy simulation and planning for prostate cancer. (October 2020) - Tyagi, Neelam; Zelefsky, Michael J.; Wibmer, Andreas; Zakian, Kristen; Burleson, Sarah; Happersett, Laura; Halkola, Aleksi; Kadbi, Mo; Hunt, Margie
Abstract: Background and purpose: Magnetic Resonance (MR)-only planning has been implemented clinically for radiotherapy of prostate cancer. However, fewer studies exist regarding the overall success rate of MR-only workflows. We report on successes and challenges of implementing MR-only workflows for prostate. Materials and methods: A total of 585 patients with prostate cancer underwent an MR-only simulation and planning between 06/2016 – 06/2018. MR simulation included images for contouring, synthetic-CT generation and fiducial identification. Workflow interruptions occurred that required a backup CT, a re-simulation or an update to our current quality assurance (QA) process. The challenges were prospectively evaluated and classified into synthetic-CT generation, motion/artifacts in the MRs, fiducial QA and bowel preparation guidelines. Results: MR-only simulation was successful in 544 (93.2%) patients. In seventeen patients (2.9%), reconstruction of synthetic-CT failed due to patient size, femur angulation, or failure to determine the body contour. Twenty-four patients (4.1%) underwent a repeat/backup CT scan because of artifacts on the MR such as image blur due to patient motion or biopsy/surgical artifacts that hampered identification of the implanted fiducial markers. In patients requiring large coverage due to nodal involvement, inhomogeneity artifacts were resolved by using a two-stack acquisition and adaptive inhomogeneity correction. Bowel preparation guidelines were modified to address frequent rectum/gas issues due to longer MR scan time. Conclusions: MR-only simulation has been successfully implemented for a majority of patients in the clinic. However, MR-CT or CT-only pathway may still be needed for patients where MR-only solution fails or patients with MR contraindications.